2016
DOI: 10.1038/srep38551
|View full text |Cite
|
Sign up to set email alerts
|

Association between neutrophil-to-lymphocyte ratio and differentiated thyroid cancer: a meta-analysis

Abstract: The association between neutrophil-to-lymphocyte ratio (NLR) and differentiated thyroid cancer (DTC) is undecided. To rectify this question, we conducted a systematic meta-analysis based on 7 prospective cohort studies published between 2013 and 2015, comprising 7349 patients. Six of these cohorts included pretreatment (baseline) NLR data for patients with thyroid nodules. The meta-analysis of these 6 cohorts showed that the NLR of patients with DTC (4617 cases) was statistically similar to patients with benig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 19 publications
1
51
0
Order By: Relevance
“…Neutrophils, lymphocytes, and platelets play a role in the control of inflammation, and systemic inflammation is associated with alterations in the quantity and composition of circulating blood cells, such as neutrophilia, lymphopenia, and thrombocytosis . Mean platelet volume (MPV), neutrophil‐to‐lymphocyte ratio (NLR), and platelet‐to‐lymphocyte ratio (PLR) have recently been investigated as new inflammatory markers in many inflammatory, cardiovascular, and malignant diseases . MPV is the volume of the average circulating platelets in femtoliters and is a marker of platelet activation that is known to be associated with inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils, lymphocytes, and platelets play a role in the control of inflammation, and systemic inflammation is associated with alterations in the quantity and composition of circulating blood cells, such as neutrophilia, lymphopenia, and thrombocytosis . Mean platelet volume (MPV), neutrophil‐to‐lymphocyte ratio (NLR), and platelet‐to‐lymphocyte ratio (PLR) have recently been investigated as new inflammatory markers in many inflammatory, cardiovascular, and malignant diseases . MPV is the volume of the average circulating platelets in femtoliters and is a marker of platelet activation that is known to be associated with inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…The systemic inflammatory response, a subject of intensive research, suppresses the activity of host immune cells through promoting microvascular regeneration, which facilitates the proliferation and differentiation of tumor cells, thus enhancing the invasion of tissues by tumor cells (13)(14)(15). The neutrophil-to-lymphocyte ratio (NLR) serves as an accurate and reliable index of systemic inflammation and, thus, serves as a systemic marker of inflammation (16). Furthermore, strong evidence indicates that a higher NLR is associated with the growth and migration of malignant cells.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in 2016, a meta-analysis of 6 prospective cohorts with 6283 differentiated thyroid cancer patients revealed no difference in NLR 6 between patients with cancer and benign nodules with a mean difference of 0.19 (95% CI: -0.09-0.46, p<0.001). This meta-analysis concluded that an elevated NLR could not predict differentiated thyroid cancer, however well-designed large studies were needed [27].…”
Section: Resultsmentioning
confidence: 98%